2023
DOI: 10.1038/s41419-023-05674-7
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 regulates Mybl2 via HeyL to limit proliferation and tumor initiation in breast cancer

Abstract: Notch signaling is a conserved signaling pathway that participates in many aspects of mammary gland development and homeostasis, and has extensively been associated with breast tumorigenesis. Here, to unravel the as yet debated role of Notch3 in breast cancer development, we investigated its expression in human breast cancer samples and effects of its loss in mice. Notch3 expression was very weak in breast cancer cells and was associated with good patient prognosis. Interestingly, its expression was very stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Further, it was reported that miR-218-5p can simultaneously bind hsa_circ_0058124 and Numb, a significant Notch signaling suppressor. Notch signaling, in a multitude of cancer types, functions to prevent initiation and propagation of tumorigenesis and serves as an extensive cell cycle regulator via Mybl2 [71]. The expression level of Numb was detected in PTC patient samples via qRT-PCR and found to be significantly upregulated along with hsa_circ_0058124, confirming a ceRNA axis of regulation between these three transcripts.…”
Section: Role Of Hsa_circ_0058124 In Thyroid Cancermentioning
confidence: 85%
“…Further, it was reported that miR-218-5p can simultaneously bind hsa_circ_0058124 and Numb, a significant Notch signaling suppressor. Notch signaling, in a multitude of cancer types, functions to prevent initiation and propagation of tumorigenesis and serves as an extensive cell cycle regulator via Mybl2 [71]. The expression level of Numb was detected in PTC patient samples via qRT-PCR and found to be significantly upregulated along with hsa_circ_0058124, confirming a ceRNA axis of regulation between these three transcripts.…”
Section: Role Of Hsa_circ_0058124 In Thyroid Cancermentioning
confidence: 85%
“…Dysregulation of Notch3 has been associated with numerous cancers [ 44 , 45 ], impacting tumor aggressiveness, maintenance, and resistance to chemotherapy [ 46 48 ]. In addition, studies found that NOTCH3 can have a role in orchestrating antitumoral activity by inducing the expression of PD-1 [ 49 , 50 ].…”
Section: Case Presentation and Discussionmentioning
confidence: 99%